Comparison Theorems of Spectral Radius for Splittings of Matrices - Cui-Xia Li; Su-Hua Li (Journal of Applied Mathematics)
A class of the iteration method from the double splitting of coefficient matrix for solving the linear system is further investigated. By structuring a new matrix, the iteration matrix of the corresponding double splitting iteration method is presented. On the basis of convergence and comparison theorems for single splittings, we present some new convergence and comparison theorems on spectral radius for splittings of matrices.